PERAN KOMUNIKASI PADA PENANGANAN KESEHATAN MENTAL IBU PASCA PERSALINAN - Lubis, Lubis; Setiyono, Budi; Kushandajani, Kushandajani; Sardini, Nur Hidayat (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2024)
Abstract: The role of communication is very important in providing treatment to postpartum maternal mental health in the form of providing Educational Information Communication (EIC) and counseling. Providing the right information when providing EIC and counseling will have a positive impact on the mental health of postpartum mothers. The research used qualitative exploratory studies. Data was collected through in-depth, semi-structured, and face-to-face interviews. The data were analyzed using inductive content analysis. The sampling method is based on purposefully select of 6 health workers in December 2024. The results showed that informants consisted of 4 midwives, 1 Head of Public health center and 1 mental nurse interviewed. There are 4 (four) themes based on communication components, namely the source of communication, the message conveyed, the media used, the recipient of the message, and the reciprocal effects of the message that has been delivered. From these four themes, it was found that health workers, especially midwives, have not provided IEC material or counseling that is still not appropriate in accordance with the mental health conditions of postpartum mothers. The communication media used is also still limited. So there is a need for training for midwife health workers to be able to provide good communication according to the needs of mothers after childbirth.Abstrak: Peran komunikasi sangat penting dalam memberikan penanganan kepada kesehatan mental ibu pasca persalinan berupa pemberian Komunikasi Informasi Edukasi (KIE) dan konseling. Pemberian informasi yang tepat saat memberikan KIE dan konseling akan berdampak positif terhadap kesehatan mental ibu pasca persalinan. Penelitian menggunakan studi eksploratif kualitatif. Data dikumpulkan melalui wawancara mendalam semi terstruktur dan tatap muka. Data dianalisis menggunakan analisis conten induktif. Metode pengambilan sampel berdasarkan purposefully select terhadap 6 orang tenaga kesehatan pada bulan desember 2024. Hasil penelitian menunjukan bahwa informan terdiri dari 4 orang bidan, 1 Kepala Puskesmas dan 1 orang perawat jiwa yang diwawancarai. Terdapat 4 (empat) tema berdasarkan komponen komunikasi yaitu sumber komunikasi, pesan yang disampaikan, media yang digunakan, penerima pesan, dan efek timbal balik dari pesan yang sudah disampaikan. Dari empat tema tersebut didapatkan bahwa tenaga kesehatan khususnya bidan belum memberikan materi KIE atau konseling yang masih kurang tepat sesuai dengan kondisi kesehatan mental ibu pasca persalinan. Media komunikasi yang digunakan juga masih terbatas. Sehingga perlu adanya pelatihan kepada tenaga kesehatan bidan untuk dapat memberikan komunikasi yang efektif sesuai kebutuhan ibu pasca persalinan.